Revisiting the impact of financial development on economic growth: the case of Turkey. (12th May 2020) - Gulay, Emrah; Cowley, Joshua D.
This study re-examines the impact of financial development on economic growth using time series data covering the period 2006 to 2015 in Turkey. The existing literature on the relationship between economic growth and financial development has focused on various proxies for financial development. When utilising different proxies for financial development, the results of the models varied. The aim of this paper is to use one index, which represents financial development, without making any random decisions on the selection of financial development proxies. Our results confirm an unambiguously positive relationship between economic growth and financial development in Turkey. Using the bounds test for cointegration, this study finds that the effect of the Arab Spring is captured in the short-run dynamic model and it has a temporary impact on the instability of coefficients in terms of the link between economic growth and financial development in Turkey.